2017
DOI: 10.1101/239244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine-grained habitat-associated genetic connectivity in an admixed population of mussels in the small isolated Kerguelen Islands

Abstract: Reticulated evolution -i.e. secondary introgression / admixture between sister taxa-is increasingly recognized as playing a key role in structuring infra-specific genetic variation and revealing cryptic genetic connectivity patterns. When admixture zones coincide with ecological transitions, the connectivity patterns often follow environmental variations better than distance and introgression clines may easily be confounded with local adaptation signatures. The Kerguelen mussels is an ideal system to investiga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…Estimates are also consistent with previous studies proposing separation times between northern and southern hemisphere Mytilus species ~0.5 to 1.3 million years ago based on mitochondrial loci (Gérard et al, ; Hilbish et al, ). More broadly, our findings support a scenario of parallel transequatorial migrations leading to the origins of southern hemisphere mussels, that is M. planulatus in Australasia which is more related to M. galloprovincialis (this study) and M. platensis in South America and the Kerguelen Islands which is more related to M. edulis in the northern hemisphere (Fraïsse, Haguenauer, et al, ). Under this scenario, however, mitochondrial introgression swamping following secondary contact between M. galloprovincialis and M. edulis (Fraïsse, Haguenauer, et al, ; Gérard et al, ) has been proposed to reconcile incongruent patterns of deep divergence at mitochondrial loci and reciprocal monophyly (with northern haplotypes) for all southern hemisphere lineages (Gérard et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Estimates are also consistent with previous studies proposing separation times between northern and southern hemisphere Mytilus species ~0.5 to 1.3 million years ago based on mitochondrial loci (Gérard et al, ; Hilbish et al, ). More broadly, our findings support a scenario of parallel transequatorial migrations leading to the origins of southern hemisphere mussels, that is M. planulatus in Australasia which is more related to M. galloprovincialis (this study) and M. platensis in South America and the Kerguelen Islands which is more related to M. edulis in the northern hemisphere (Fraïsse, Haguenauer, et al, ). Under this scenario, however, mitochondrial introgression swamping following secondary contact between M. galloprovincialis and M. edulis (Fraïsse, Haguenauer, et al, ; Gérard et al, ) has been proposed to reconcile incongruent patterns of deep divergence at mitochondrial loci and reciprocal monophyly (with northern haplotypes) for all southern hemisphere lineages (Gérard et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, variation across the nuclear genomic background of Australian mussels alongside northern hemisphere taxa validated strong genetic affinities to M. galloprovincialis , suggesting a closer genetic relationship to the invasive taxon than implicated by mitochondrial loci (e.g. Fraïsse, Haguenauer, et al, ; Hilbish et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be noted that independent contacts can show reversed associations with the environment, in agreement & Wenne, 2018; McDonald, Seed, & Koehn, 1991;Saarman & Pogson, 2015;Zbawicka, Trucco, & Wenne, 2018). By contrast, we only know of a few cases of M. edulis introductions -either transient or successful -into non-native areas (Casoli et al, 2016;Crego-Prieto et al, 2015;Fraïsse, Haguenauer, et al, 2018). Branch and Steffani (2004) reported that observed introductions of M. galloprovincialis happened close to large shipping ports, with a secondary range expansion from these points.…”
Section: Introductionsupporting
confidence: 55%